I am to solve a problem:

$\forall x \exists y \neg P(x,y) \rightarrow \exists x \forall y Q(x,y)$

I'm getting rid of implication:

$\exists x \forall y P(x,y) \lor \exists x \forall y Q(x,y)$

And now I'm using this formula: $\exists x A(x) \lor \exists B(x)$ = $\exists x( A(x) \lor B(x))$

$\exists x (\forall y P(x,y) \lor \forall y Q(x,y))$

Then I resolve variable conflicts: y->t

$\exists x (\forall y P(x,y) \lor \forall t Q(x,t))$

And moving all quantifiers to the very begining

$\exists x \forall y \forall t (P(x,y) \lor Q(x,t)))$

The existence quantifier should be changed to the constanta: x->c

$ \forall y \forall t (P(c,y) \lor Q(c,t)))$

And then eliminating the $\forall$ quantifiers

$(P(c,y) \lor Q(c,t))$

Am I right at my solution? Can anybody please check the answer?


Yes. Each step is well reasoned and checks out okay.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.